2010
DOI: 10.1183/09031936.00077210
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids and lower lung function decline in young children with cystic fibrosis

Abstract: , on behalf of the members of the Belgian CF Registry ABSTRACT: A recent American registry analysis in cystic fibrosis (CF) children showed less lung function decline after starting inhaled corticosteroid (ICS) use. We therefore examined the influence of ICS treatment on lung function in Belgian CF patients.Data from patients o6 yrs of age were eligible, provided entries on lung function, height and ICS use were available in two consecutive years. Data after oral steroid use or transplant were excluded.852 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
(27 reference statements)
4
21
0
1
Order By: Relevance
“…FEV1% was about 10% better in the intervention group 2 years before start of the study, moreover, all pulmonary testing parameters were getting worst in the intervention group before inclusion. The finding of a more important decrease in the intervention group who had better FEV1% (≥90%) in the two-years period prior to the study is coherent with the recent findings by de Boeck et al who described a significant higher annual rate of decline of 1.9% predicted in a group of individuals with an FEV1% ≥90% predicted compared with 0.4% predicted in a group with FEV1% < 90% predicted [14]. In this regard of a faster decline of FEV1% predicted in the intervention group prior to the intervention, with an improvement during the study period, most likely due to the intervention (TPE), becomes even more important.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…FEV1% was about 10% better in the intervention group 2 years before start of the study, moreover, all pulmonary testing parameters were getting worst in the intervention group before inclusion. The finding of a more important decrease in the intervention group who had better FEV1% (≥90%) in the two-years period prior to the study is coherent with the recent findings by de Boeck et al who described a significant higher annual rate of decline of 1.9% predicted in a group of individuals with an FEV1% ≥90% predicted compared with 0.4% predicted in a group with FEV1% < 90% predicted [14]. In this regard of a faster decline of FEV1% predicted in the intervention group prior to the intervention, with an improvement during the study period, most likely due to the intervention (TPE), becomes even more important.…”
Section: Discussionsupporting
confidence: 80%
“…Identifier le mode d'action des enzymes pancréatiques" with a true/false questionnaire) [14] and a CD ("Un voyage à travers l'appareil digestif " [7]). In regards of quality of life, no trend was seen in the CFQ r .…”
Section: Discussionmentioning
confidence: 99%
“…This follows an earlier report with similar findings based on North American CF registry data [13]. The data from Belgium show that while there is a beneficial effect overall, the benefit from inhaled corticosteroids was restricted to children between the ages of 6 and 12 yrs; however, no data were available from children under the age of 6 yrs [12]. The registry data demonstrated that the mean decline in FEV1 % pred in children aged 6-12 yrs was 1.37%.…”
supporting
confidence: 73%
“…in national CF data registries. In the current edition of the European Respiratory Journal, DE BOECK et al [12] report data from the Belgian national CF data registry that show a small but significant decrease in lung function decline, expressed as forced expiratory volume in 1 s (FEV1) % predicted, in children taking regular inhaled corticosteroids. This follows an earlier report with similar findings based on North American CF registry data [13].…”
mentioning
confidence: 99%
“…Several medications have been associated to slowing down the rate of FEV 1 decline: dornase alpha (Konstan et al, 2011), ibuprofen (Konstan et al, 1995;, azithromycin (Hansen et al, 2005) and inhaled corticosteroids (De Boeck et al, 2011). This does not mean that all patients will benefit from them.…”
Section: Good Care Management Of Cfmentioning
confidence: 99%